The effects of 11 yr of CO2 enrichment on roots in a Florida scrub‐oak ecosystem. Issue 3 (25th March 2013) - Day, Frank P.; Schroeder, Rachel E.; Stover, Daniel B.; Brown, Alisha L. P.; Butnor, John R.; Dilustro, John; Hungate, Bruce A.; Dijkstra, Paul; Duval, Benjamin D.; Seiler, Troy J.; Drake, Bert G.; Hinkle, C. Ross
Summary: Uncertainty surrounds belowground plant responses to rising atmospheric CO2 because roots are difficult to measure, requiring frequent monitoring as a result of fine root dynamics and long‐term monitoring as a result of sensitivity to resource availability. We report belowground plant responses of a scrub‐oak ecosystem in Florida exposed to 11 yr of elevated atmospheric CO2 using open‐top chambers. We measured fine root production, turnover and biomass using minirhizotrons, coarse root biomass using ground‐penetrating radar and total root biomass using soil cores. Total root biomass was greater in elevated than in ambient plots, and the absolute difference was larger than the difference aboveground. Fine root biomass fluctuated by more than a factor of two, with no unidirectional temporal trend, whereas leaf biomass accumulated monotonically. Strong increases in fine root biomass with elevated CO2 occurred after fire and hurricane disturbance. Leaf biomass also exhibited stronger responses following hurricanes. Responses after fire and hurricanes suggest that disturbance promotes the growth responses of plants to elevated CO2 . Increased resource availability associated with disturbance (nutrients, water, space) may facilitate greater responses of roots to elevated CO2 . The disappearance of responses in fine roots suggests limits on the capacity of root systems to respond to CO2 enrichment.